Análise reconstitutiva do sentido da dialética em Lev Vigotski - Wrasse, Dílson (2017)
The present work analyzes the concept of dialectics at Lev Semionovich Vigotski (1896-1934) with regard to the body of his work and, on the other hand, his most important theoretical influences in the field of gnoseology and the theory of knowledge, and explains the theoretical foundations for the construction of a dialectical psychology. Therefore, we subdivide our work into an introductory chapter, followed by three parts: In the first chapter, we particularly emphasize the hermeneutic method used to analyze the works of the author, since the largest part of the collection still exist only in Russian, partly in English and Spanish, and to a lesser extent in Portuguese. In the first part, "The State of Vigotski´s Hermeneutic Art", we present analyzes of the historical context, the biography, the characteristics of the work and the publicizing policy. In the second part, "The Adventures of Dialectics", we discuss the most important philosophical conversation partners of the author (Immanuel Kant, Georg W. F. Hegel, Ludwig Feuerbach, Karl Marx, Friedrich Engels and Vladimir Ilich Lênin) and the discussion about dialectic in the second half of the twentieth. The third part presents the detailed analysis of some selected works and shows how the maturation process of the dialectical logic and the historical-dialectical materialism are expressed in the field of epistemology. The dispute between the two epistemic theories of idealism and materialism qualifies the author in the consolidation of a dialectical psychology, which, together with revolutionary practice, contributes to building a new society and a new human being. In this work, we support the thesis that Lev Semionovich Vigotski, without referring to the epistemological dispute and without the foundations of historical dialectical materialism, would not have elucidated the methodological limits of contemporary psychology and thus did not create the most important methodological basis for the understanding of the human psyche